COHESION DEVICES ON THE LYRICS OF BOB MARLEY’S SONGS - WIBIARTA, ARDITYA (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Cohesion, Cohesion Devices, Lyric, Bob Marley. This study is about cohesion devices found in the lyrics of Bob Marley’s songs. The objectives are to reveal the kinds of grammatical and lexical cohesion used in the lyrics of Bob Marley’s songs.In conducting this study, the researcher uses descriptive qualitative method, because the data in the form of words, phrases, and sentences. The data of this study is taken form the lyrics of five Bob Marley’s songs, they are: Get Up, Stand Up, One Love, Redemption Song, War, Revolution. In analyzing the data, the researcher uses Halliday and Hasan’s theory to find the kinds of grammatical cohesion and Renkema’s theory to find the kinds of lexical cohesion.The result of this study shows the type of grammatical cohesion which mostly appeared are demonstrative and personal reference, while lexical cohesion which is mostly used is repetition Both cohesion devices have different function.The researcher suggests English learners to consider the usage of cohesion devices for practicing writing and speaking in order to increase their writing andspeaking skills. The suggestion for the lecturers to enrich their teaching materials by using this study as reference and the researcher also suggests the next researcher to take the data from written text to ease the research and conduct a more detailed and deeper analysis by comparing and combining this research with another research.